A history of Grahamstown, 1918-1945 - Torlesse, Ann Catherine Marjorie (Rhodes University, Faculty of Humanities, Department of History, 1993)
This study in local history describes socio-economic developments in Grahamstown between 1918 - 1945, and analyses the extent to which these developments mirrored trends in the macrocosm. During these years the city failed to become ndustrialised, but enhanced her reputation as an eminent educational centre. Despite being financially handicapped, the City Council undertook large public works schemes for the provision of essential services, such as electricity and an adequate supply of water. In addition a water-borne sewerage scheme was introduced, and roads were repaired and tarred. The influx of a large number of poor rural Blacks into the urban area placed a considerable strain on the city's health services, and housing projects had to be implemented. Local political affiliations and race relations are examined against the background of national developments, especially the growing entrenchment by the State of the policy of segregation. Attention is also devoted to the impact upon the community of international political crises. The cultural and sporting pursuits, as well as the entertainments enjoyed by Grahamstonians, are investigated; and a picture of the local "mentalite" is presented.
Keywords: Grahamstown (South Africa) -- History; Grahamstown (South Africa) -- Economic conditions